THE LEVEL OF STUDY OF RODENTS IN THE CONDITIONS OF KARAKALPAK REPUBLIC - Paluanova, Gulmira Jolimbetovna; Qarjawbaeva, Kamila Baxtiyarovna; Qurbaniyazov, Atabek Sabirbayevich (SCIENCE and SOCIETY, 2026)
The article presents research by scientists on assessing the scale of rodent impact on public health and agriculture in our republic, as well as increasing populations of harmful species alongside the decline in the number of rare species of theriofauna representatives under the influence of anthropogenic factors in heavily developed areas. Important scientific and practical studies are presented, such as determining the species composition of mouse-like rodents, studying their distribution in various landscapes, and substantiating their ecology.
Keywords: biotope; Lower Amudarya State Biosphere Reserve; reserve; Ustyurt; Kyzylkum; Baday-Tugay; Southern Aral Sea; fauna; rodents; lamellar-toothed rat; Trans-Caspian ground squirrel; house mouse